The majority of currently circulating human immunodeficiency virus type 1 clade B viruses fail to prime cytotoxic T-lymphocyte responses against an otherwise immunodominant HLA-A2-restricted epitope: implications for vaccine design. - Altfeld, M; Allen, T; Kalife, E; Frahm, N; Addo, M; Mothe, B; Rathod, A; Reyor, L; Harlow, J; Yu, X; Perkins, B; Robinson, L; et al. (2005)
Human immunodeficiency virus type 1 (HIV-1) mutates to escape immune selection pressure, but there is little evidence of selection mediated through HLA-A2, the dominant class I allele in persons infected with clade B virus. Moreover, HLA-A2-restricted responses are largely absent in the acute phase of infection as the viral load is being reduced, suggesting that circulating viruses may lack immunodominant epitopes targeted through HLA-A2. Here we demonstrate an A2-restricted epitope within Vpr (Vpr59-67) that is targeted by acute-phase HIV-1-specific CD8+ T cells, but only in a subset of persons expressing HLA-A2. Individuals in the acute stage of infection with viruses containing the most common current sequence within this epitope (consensus sequence) were unable to mount epitope-specific T-cell responses, whereas subjects infected with the less frequent I60L variant all developed these responses. The I60L variant epitope was a stronger binder to HLA-A2 and was recognized by epitope-specific T cells at lower peptide concentrations than the consensus sequence epitope. These data demonstrate that HLA-A2 is capable of contributing to the acute-phase cytotoxic T-lymphocyte response in infected subjects, but that most currently circulating viruses lack a dominant immunogenic epitope presented by this allele, and suggest that immunodominant epitopes restricted by common HLA alleles may be lost as the epidemic matures.